The effects of the learning environment and digital literacy on students’ entrepreneurial intention: The mediating role of self-efficacy in the digital creative economy - Heny Ratnaningtyas; Michael Khrisna Aditya; Eduard Rudolf Pangkerego (Jurnal Pendidikan Vokasi, 2025)
The educated unemployment rate in Indonesia remains high despite a national downward trend, underscoring the need for students to pursue entrepreneurship to create jobs. This study analyses the effects of the learning environment and digital literacy on entrepreneurial intention, with self-efficacy as a mediating variable. This quantitative study employed an explanatory approach and involved 350 students from universities in Jakarta, Bandung, and Surabaya who had completed entrepreneurship courses.  The research statistical method employed path analysis, analyzed using SmartPLS. Data were collected using a five-point Likert-scale questionnaire. The learning environment and digital literacy significantly influenced self-efficacy, with digital literacy emerging as the most dominant factor. Self-efficacy significantly affected entrepreneurial intention and mediated the relationships between the learning environment and digital literacy and entrepreneurial intention. Meanwhile, digital literacy did not directly influence entrepreneurial intention in the absence of self-efficacy. The sample was limited to students in three major cities and to those enrolled in entrepreneurship courses; thus, generalization should be made with caution. Future research should expand regional coverage, incorporate institutional and socio-economic variables, and employ longitudinal designs to capture changes in entrepreneurial intention over time. Universities should enrich authentic learning ecosystems such as project-based learning, mentorship, and incubation, and strengthen applied digital literacy to enhance students' self-efficacy. Training that emphasizes digital competencies and real entrepreneurial experience is likely to be more effective at fostering entrepreneurial intention.